The Treasures of the Borderzone - Bagina, Elena (project baikal, 2018)
Sergey Astapov, descendent of a sculptor’s family from St Petersburg, is ironic and quick-witted. His academic education allows for working in different genres. But in any genre, he aims at doing his job to the best of his ability. He calls his style ‘enigmatic realism’. The mythologemas known from childhood acquire a new dimension in Sergey Astapov’s compositions. The sculptor’s monumental works beautify St Petersburg, and his chamber sculptures are kept in museums and private collections.